The codification long-term goal and strategy development of intramuralprograms of Islamic Azad Universities in North West of Iran - Hossein Bayat; Seyed Mansour Mousavi; Nasser Taghibigloo (Turkish Journal of Kinesiology, 2019)
This study aimed to perform the SWOT Internal and external strategic analysis of intramural programs of Islamic Azad Universities in North West of Iran. This was a descriptive case study. The population consisted of all physical education managers of Islamic Azad Universities in North West of Iran (N=36). Due to limited population, all 36 managers were selected as a sample. The data were collected through interview, questionnaire, library content, and literature review. The researcher-made questionnaire consisted of 50 questions about strengths, weaknesses, opportunities, and threats of intramural programs of Islamic Azad Universities in North West of Iran. Its validity was confirmed by a number of experts; also, its reliability was confirmed by using Cronbach's alpha (alpha = 96%). After collecting the data, the factors were ranked. Based on the findings, the intramural programs of Islamic Azad Universities in North West of Iran have 72 units and a total of 199368 students. The strategic position was determined to be in WT in SWOT matrix. The organizations which determine WT strategies are defensive; they aim to reduce internal weaknesses and avoid threats of the external environment. After determining strategic position, the WO, WT, SO, and ST were developed.